Jung’s Psychoid Monism - Pylkkö, Pauli (Journal of analytical psychology, 2023)
Jung’s final psychoid theory of archetypes was an additional attempt to find a solution to the philosophical problem of how to relate mind and matter. In the following essay Jung’s solution is summarized by a set of 17 theses, and Jung’s philosophy will be called psychoid monism. According to psychoid monism, what ultimately and primarily is, is the psycho‐physically neutral domain of instinctual experience. The origin of this view can be traced back to Post‐Kantian German Idealism (Schopenhauer, Schelling, Hölderlin), and a systematization of the view requires a dialectic approach and, in particular, contradiction‐tolerant dialectic logic. La dernière théorie psychoïde des archétypes de Jung était une tentative supplémentaire pour trouver une solution au problème philosophique de comment mettre en lien l’esprit et la matière. Dans cet article, la solution de Jung est résumée en une série de 17 thèses, et la philosophie de Jung sera appelée le monisme psychoïde. Selon le monisme psychoïde, ce qui est – de manière ultime et première – c’est le domaine psycho‐physique neutre de l’expérience instinctuelle. L’origine de cette perspective trouve son origine dans l’Idéalisme Allemand Postkantien (Schopenhauer, Schelling, Hölderlin). Une systématisation de cette perspective requiert une approche dialectique et tout particulièrement une logique dialectique qui tolère la contradiction. Jungs endgültige psychoide Theorie der Archetypen war ein zusätzlicher Versuch, eine Lösung für das philosophische Problem zu finden, wie man Geist und Materie aufeinander bezieht. In der folgenden Arbeit wird Jungs Lösung durch einen Satz von 17 Thesen zusammengefaßt. Jungs Philosophie wird als psychoider Monismus bezeichnet. Nach dem psychoiden Monismus ist das, was letztendlich und in erster Linie ist, der psycho‐physisch neutrale Bereich der instinktiven Erfahrung. Der Ursprung dieser Sichtweise kann auf den postkantianischen deutschen Idealismus (Schopenhauer, Schelling, Hölderlin) zurückgeführt werden. Eine Systematisierung dieser Ansicht erfordert einen dialektischen Ansatz und insbesondere eine widerspruchstolerante dialektische Logik. La teoria psicoide degli archetipi di Jung fu un ulteriore tentativo di trovare una soluzione al problema filosofico di come connettere mente e materia. Nel presente articolo, la soluzione di Jung viene riassunta da una serie di 17 tesi, e la filosofia di Jung viene definita monismo psicoide. Questa prospettiva afferma, in definitiva e principalmente, il dominio psichicamente e fisicamente neutrale dell’esperienza degli istinti. L’origine di questa visione può essere rintracciata fino all’idealismo tedesco post‐kantiano (Schopenhauer, Schelling, Hölderlin) e la sua sistematizzazione richiede un approccio dialettico e, più in particolare, una logica dialettica che sia tollerante delle contraddizioni. Итоговая психоидная теория архетипов Юнга стала еще одной попыткой найти решение философской проблемы связи между разумом и материей. В статье в краткой форме в виде 17 тезисов приводится способ ее решения, предложенный Юнгом, а его философия названа психоидным монизмом. Согласно психоидному монизму, то, что существует в конечном итоге и изначально, это психофизически нейтральная сфера инстинктивного ощущения. Истоки этого взгляда можно проследить в посткантианском немецком идеализме (Шопенгауэр, Шеллинг, Гёльдерлин), а для его систематизации необходим диалектический подход и, в частности, толерантная к противоречиям диалектическая логика. La teoría final psicoide de Jung sobre los arquetipos fue un intento adicional de encontrar una solución al problema filosófico de cómo relacionar mente y materia. En el siguiente artículo, la solución de Jung se resume en un conjunto de 17 tesis, y la filosofía de Jung se denominará monismo psicoide. Según el monismo psicoide, de lo que principalmente y en última instancia se trata, es del dominio psicofísicamente neutro de la experiencia instintiva. El origen de este punto de vista se remonta al Idealismo alemán postkantiano (Schopenhauer, Schelling, Hölderlin), y su sistematización requiere un enfoque dialéctico y, en particular, una lógica dialéctica tolerante con las contradicciones. 荣格的心理活力一元论 荣格最后提出的关于原型的心理活力的理论, 是关于解决心与物的关联这一哲学问题的又一次尝试。在下面的文章中, 荣格的解决方案被一套17个论点所概括, 荣格的这一哲学将被称为心理活力一元论。根据心理活力一元论, 最重要和首要的是, 心理‐物理的中间领域是不是本能的经验。这一观点的起源可以追溯到后康德式的德国理想主义 (叔本华、谢林、荷尔德林), 而这一观点的系统化需要辩证法, 特别是需要可以容忍矛盾的辩证逻辑。